The association between blood pressure and long-term outcomes of patients with ischaemic cardiomyopathy with and without surgical revascularization: an analysis of the STICH trial - Andersson, Bert (Eur Heart J, 2018)
AIMS: Hypertension (HTN) is a well-known contributor to cardiovascular disease, including heart failure (HF) and coronary artery disease, and is the leading risk factor for premature death world-wide. A J- or U-shaped relationship has been suggested between blood pressure (BP) and clinical outcomes in different studies. However, there is little information about the significance of BP on the outcomes of patients with coronary artery disease and left ventricular dysfunction. This study aimed to determine the relationship between BP and mortality outcomes in patients with ischaemic cardiomyopathy. METHODS AND RESULTS: The influence of BP during a median follow-up of 9.8 years was studied in a total of 1212 patients with ejection fraction ≤35% and coronary disease amenable to coronary artery bypass grafting (CABG) who were randomized to CABG or medical therapy alone (MED) in the STICH (Surgical Treatment for Ischaemic Heart Failure) trial. Landmark analyses were performed starting at 1, 2, 3, 4, and 5 years after randomization, in which previous systolic BP values were averaged and related to subsequent mortality through the end of follow-up with a median of 9.8 years. Neither a previous history of HTN nor baseline BP had any significant influence on long-term mortality outcomes, nor did they have a significant interaction with MED or CABG treatment. The landmark analyses showed a progressive U-shaped relationship that became strongest at 5 years (χ(2) and P-values: 7.08, P = 0.069; 8.72, P = 0.033; 9.86; P = 0.020; 8.31, P = 0.040; 14.52, P = 0.002; at 1, 2, 3, 4, and 5-year landmark analyses, respectively). The relationship between diastolic BP (DBP) and outcomes was similar. The most favourable outcomes were observed in the SBP range 120–130, and DBP 75–85 mmHg, whereas lower and higher BP were associated with worse outcomes. There were no differences in BP-lowering medications between groups. CONCLUSION: A strong U-shaped relationship between BP and mortality outcomes was evident in ischaemic HF patients. The results imply that the optimal SBP might be in the range 120–130 mmHg after intervention, and possibly be subject to pharmacologic action regarding high BP. Further, low BP was a marker of poor outcomes that might require other interactions and treatment strategies. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00023595.